Review of A 'Proper' Woman? One Woman's Story of Success and Failure in Academia, by Pat O'Connor - Curt Rice (Review of Irish Studies in Europe, 2025)
Review of A 'Proper' Woman? One Woman's Story of Success and Failure in Academia, by Pat O'Connor (Bern and London: Peter Lang, 2024), 223 pp., ISBN: 978-1-80374-305-9, €32.60